Main Agroecological Structure (MAS) as a tool for resilient farm planning - Clavijo, Neidy; Gómez, Thomas (2023)
In the endeavor to co-design cocoa and livestock low-emission agri-food systems that foster peace, sustainability, and resilience to climate change in the Caquetá department of Colombia, understanding the intricate biophysical and social dynamics of these agroecosystems is of paramount importance. This comprehension is essential for gauging the resilience of these systems in the face of climate change.